Allometric scales: a fair approach in process assessment in human movement sciences - Moncada Jiménez, José (2011)
The purpose of the study was to compare the running time in sixth graders from Costa Ricaand the United States and to investigate the influence of body mass on running time.Students (N = 274) was measured body massand time to travel 1609 m walk. Statistical analyzes included 2 x 2 factorial ANOVA (country x gender) for body mass variables and race time, andregression analysis to create an index scores adjusted race time and set aside theconfounding effect of body mass. It was found that the nor-dren and Rican girls had lowerbody mass and ran the 1609 m faster than theirAmerican counterparts (p <0.05). In both samples, the children who had higherbody mass tended to be penalized by the methodtraditional to assign scores. Therefore, the calculatedcorrection index, which race times adjusted taking into account differences in body mass. We conclude that the allometric scales technique is just one tool that can be incorporated intothe evaluation process in the area of ​​human movement science, and recommends the development ofrules that take into account the influence of the massParticipants body as well as the application of theAllometric scales to other physical fitness tests.